EQUALITY THROUGH EXCLUSION? TOWARDS A NEW CONCEPTUALIZATION OF DEMOCRATIC EXCLUSION IN THE CONTEXT OF DIGITAL PUBLIC VENUES - Holm, Malin Charlotte (AoIR Selected Papers of Internet Research, 2023)
In order to hinder attacks on democratic norms and processes in digital public venues, designing strategies of exclusion is a pressing concern. Nevertheless, we lack systematic studies of how digital public venues should be governed to protect – rather than undermine – democratic values through exclusion. The purpose of this contribution is to offer a systematic theorization of the concept of democratic exclusion in the context of digital public venues. I will in particular draw on two strands of literature within democratic theory which have contributed greatly to the normative theorization of democratic exclusion, but have done so in relation to other types of political settings: the works within feminist political theory on exclusion of dominant groups within parliaments (e.g. Dovi 2009; Murray 2014) and the literature on hate speech regulation and democratic self-defence against (primarily) antidemocratic parties (e.g. Müller 2016; Invernizzi Accetti and Zuckerman 2017; Malkopoulou and Kirshner 2019). First, I will analyze if and how these previous contributions can be applied to the specific context of digital public venues, where special conditions of access and visibility apply. I will then assess to what extent the platforms’ existing governing strategies and policies concerning the exclusion of problematic content or accounts are compatible with the relevant exclusion principles formulated in these works. Building on this analysis, in its final parts the study will move on to carve out more specific suggestions for how exclusion on digital venues should be governed, and what principles should guide this governance.